Elucidation of the gemcitabine transporters of Escherichia coli K-12 and gamma-proteobacteria linked to gemcitabine-related chemoresistance - Iosifidou, Nikoleta; Anagnostopoulou, Eleni; Botou, Maria; Kalfa, Eirini; Tatsaki, Ekaterini; Frillingos, Stathis (International journal of molecular sciences, 2024)
Gemcitabine (2′,2′-difluoro-2′-deoxycytidine), a widely used anticancer drug, is considered a gold standard in treating aggressive pancreatic cancers. Gamma-proteobacteria that colonize the pancreatic tumors contribute to chemoresistance against gemcitabine by metabolizing the drug to a less active and deaminated form. The gemcitabine transporters of these bacteria are unknown to date. Furthermore, there is no complete knowledge of the gemcitabine transporters in Escherichia coli or any other related proteobacteria. In this study, we investigate the complement of gemcitabine transporters in E. coli K-12 and two common chemoresistance-related bacteria (Klebsiella pneumoniae and Citrobacter freundii). We found that E. coli K-12 has two high-affinity gemcitabine transporters with distinct specificity properties, namely, NupC and NupG, whereas the gemcitabine transporters of C. freundii and K. pneumoniae include the NupC and NupG orthologs, functionally indistinguishable from their counterparts, and, in K. pneumoniae, one additional NupC variant, designated KpNupC2. All these bacterial transporters have a higher affinity for gemcitabine than their human counterparts. The highest affinity (KM 2.5-3.0 μΜ) is exhibited by NupGs of the bacteria-specific nucleoside-H+ symporter (NHS) family followed by NupCs (KM 10-13 μΜ) of the concentrative nucleoside transporter (CNT) family, 15-100 times higher than the affinities reported for the human gemcitabine transporter hENT1/SLC29A1, which is primarily associated with gemcitabine uptake in the pancreatic adenocarcinoma cells. Our results offer a basis for further insight into the role of specific bacteria in drug availability within tumors and for understanding the structure-function differences of bacterial and human drug transporters.
Gesehen am 16.12.2024